2001
DOI: 10.1111/j.1651-2227.2001.tb01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of sucking behavior in infants with Down's syndrome

Abstract: The aim of this study was to gain a better understanding of the development of sucking behavior in infants with Down's syndrome. The sucking behavior of 14 infants with Down's syndrome was consecutively studied at 1, 4, 8 and 12 mo of age. They were free from complications that may cause sucking difficulty. The sucking pressure, expression pressure, frequency and duration were measured. In addition, an ultrasound study during sucking was performed in sagittal planes. Although levels of the sucking pressure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 7 publications
1
47
0
1
Order By: Relevance
“…Unlike breast pumps that use only vacuum for milk expression, this pump stimulates the areola with both vacuum and compression stimuli similar to removal of milk by the baby, 11 which increases the efficiency of milk expression.…”
Section: Alekseev Et Almentioning
confidence: 99%
“…Unlike breast pumps that use only vacuum for milk expression, this pump stimulates the areola with both vacuum and compression stimuli similar to removal of milk by the baby, 11 which increases the efficiency of milk expression.…”
Section: Alekseev Et Almentioning
confidence: 99%
“…4,6,8,9 These dentofacial alterations lead to problems with sucking, swallowing, and salivation. 1,6,[9][10][11] Craniofacial growth and occlusal abnormalities may be accentuated by the interaction between genetic and environmental factors, such as breastfeeding and oral habits (pacifier sucking, finger sucking, nail biting, etc), depending on the duration, intensity, and frequency of the habit. 2,9,[12][13][14][15][16][17][18] A number of reports have suggested that nonnutritive sucking habits (usually pacifier or thumb sucking) may be responsible for some forms of malocclusion in childhood, but the role of early feeding in occlusion needs to be further evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The term ''sucking performance'' is used to describe aspects of nutritive sucking including suction, compression, and other sucking characteristics (Mizuno and Ueda, 2001). In preterm and medically compromised babies, the examination of sucking performance has improved the understanding of feeding success (Kron and Litt, 1971;Medoff-Cooper and Gennaro, 1996;Lau et al, 1997).…”
mentioning
confidence: 99%